Establishment of a Conditionally Immortalized Wilms Tumor Cell Line with a Homozygous WT1 Deletion within a Heterozygous 11p13 Deletion and UPD Limited to 11p15. - Artur Brandt; Katharina Löhers; Manfred Beier; Barbara Leube; Carmen de Torres; Jaume Mora; Parineeta Arora; Parmjit S Jat; Brigitte Royer-Pokora (PLoS ONE)
We describe a stromal predominant Wilms tumor with focal anaplasia and a complex, tumor specific chromosome 11 aberration: a homozygous deletion of the entire WT1 gene within a heterozygous 11p13 deletion and an additional region of uniparental disomy (UPD) limited to 11p15.5-p15.2 including the IGF2 gene. The tumor carried a heterozygous p.T41A mutation in CTNNB1. Cells established from the tumor carried the same chromosome 11 aberration, but a different, homozygous p.S45Δ CTNNB1 mutation. Uniparental disomy (UPD) 3p21.3pter lead to the homozygous CTNNB1 mutation. The tumor cell line was immortalized using the catalytic subunit of human telomerase (hTERT) in conjunction with a novel thermolabile mutant (U19dl89-97tsA58) of SV40 large T antigen (LT). This cell line is cytogenetically stable and can be grown indefinitely representing a valuable tool to study the effect of a complete lack of WT1 in tumor cells. The origin/fate of Wilms tumors with WT1 mutations is currently poorly defined. Here we studied the expression of several genes expressed in early kidney development, e.g. FOXD1, PAX3, SIX1, OSR1, OSR2 and MEIS1 and show that these are expressed at similar levels in the parental and the immortalized Wilms10 cells. In addition the limited potential for muscle/ osteogenic/ adipogenic differentiation similar to all other WT1 mutant cell lines is also observed in the Wilms10 tumor cell line and this is retained in the immortalized cells. In summary these Wilms10 cells are a valuable model system for functional studies of WT1 mutant cells.